To Evaluate Prevalence and Management Options of Buerger’s Disease at Tertiary Hospital. - Karam Ali Shahl, Hafeezullah Ghumro2 , MuhammadAzeem Akhund’, Altaf Hussain Ghumro , Mashooque Ali Khuwaja5, Inayat Ali Zardari6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2012)
Introduction: Burgers’ disease is a uncommon disease involving the young or middle age persons with history of smoking. Recently, it is detected that incidence has enormously increased among women. It is also observed that this condition is common in smokers as compared to non smokers but its pathophysiology is still unknown. Purpose of study: To detect the prevalence and find out the better treatment option in Buerger’s disease. Material and methods: This study was conducted in Department of Orthopedics at PMCH Nawabshah from 01“ June 2018 To 31st octomber 2019. Complete history and examination was done. History of smoking was taken specifically. Apart from routine biochemical investigations, Dopller ultrasound of the affected parts was done to find out the integration of the vessels. The treatment was decided accordingly. Results: This is study of 50 patients. There were 15 (309c) and 35 (709c) females. Of all, 45 (909a) patients were smokers and only 5 (109a) were non smokers. Age ranged from 35 to 50 years. 35 (70%) patients underwent for amputation of toes of foot. And only 15 (309a) patients were given medical therapy. Anticoagulants, vasodilators and analgesics were also given. Conclusion: It is concluded that prevalence has increased in women and amputation has better results in advanced stages.